Analisis Pengelolaan Keuangan pada Industri Pariwisata di Sumatera Utara : (Studi Kasus: Wisata Alam Syaakirah The View & Resto Desa Aek Sabaon, Kec. Marancar, Kab. Tapanuli Selatan) - Muhammad Dhio Natama Harahap; Muhammad Syukri Albani Nst; Nur Fadhilah Ahmad Hasibuan (Master Manajemen, 2024)
This research discusses financial resources and financial management which includes the stages of planning, implementation, administration, reporting, and financial accountability. This study aims to analyze financial resources and financial management in the Tourism Industry of Syaakirah The View & Resto. The method used in this study is a descriptive method with a qualitative research type. The data analysis techniques in this study are by conducting documentation, observation, and interviews. The results of this study show that the financial resources of Syaakirah The View & Resto Nature Tourism are obtained from visitor tickets, lodging, food and beverage sales, rides, parking fees, and others. Financial management at Syaakirah The View & Resto Nature Tourism has been carried out well, starting from the planning, implementation, administration, reporting, to financial accountability. Syaakirah Nature Tourism The View & Resto has made financial planning in its business. The implementation of finance in tourism has been fully carried out in accordance with the predetermined plan or target, if the target is not achieved they will make a strategy to cover the problem. Financial administration is carried out using a manual recording system using the Microsoft Excel application to record all receipts and expenditure transactions, from this administration will be recapitulation made every week and combined every month. Financial reporting on tourism has made a financial report of profit and loss on its business. Financial accountability is carried out twice a month to account for all receipts and expenses from Syaakirah Nature Tourism The View & Resto.